Integration of Cultural Literacy of The Sumenep Palace Museum in Learning Social Sciences in Primary Schools - Puspitasari, Aditya Dyah; Febrianto, Priyono Tri (Universitas Trunojoyo Madura, 2024)
Integrating cultural literacy into education is essential for creating an inclusive, equitable, and effective learning environment. Cultural literacy can be brought into learning by combining it with regional potential, such as the existence of the Sumenep Palace Museum. This research uses mixed methods research. This research was conducted in Sumenep Regency. The subjects of this research were the Sumenep Palace Museum, teachers, and 60 students of Pandian 1 State Primary School. The research results show that the Sumenep Palace Museum has the potential to be used as content for social science learning in primary schools. Both teachers and students understand the potential of the Sumenep Palace Museum so that it can become a basis for contextual learning that prioritizes local and national culture. Social science material in primary schools can be integrated with the potential of the Sumenep Palace Museum.